The Relationship Between Financial Literation Towards Users Of Loan Transacted Applications In The Millennial Generation - Retno Setyorini; Candra Wijayangka; Fikri Haikal; Nugraha Nugraha (Jurnal Manajemen Indonesia, 2021)
This study aimed to find a relationship between financial literacy and the use of loans transacted for the millennial generation—qualitative approach research method. The population in this study is the millennial generation in Bandung who have made loans transacted. The sample used was 270 people with a non-probability sampling technique with the criteria of users of online loan fintech products. The analysis technique used is a simple correlation and regression test. The results obtained show a significant influence between financial literacy variables on loans transacted with a t-value of 6,947. While the results of the correlation test state that the contribution of financial literacy to loans transacted has a contribution of 0.567, meaning that there is a fairly close relationship in terms of positive linear correlation value (r = 1), which means that every increase in financial literacy can increase the level of loans transacted. Keywords—; Fintech; Financial Literacy; Loans transacted Applications;Millenial